1975
DOI: 10.1007/bf01732015
|View full text |Cite
|
Sign up to set email alerts
|

DNA: DNA Hybridization studies in black flies

Abstract: The phylogenetic relationships of six species of black flies were investigated using the hybridization of iodinated unique DNA sequences. The thermal stability of these labelled hybrids allowed the construction of a phylogenetic tree based on base mismatch between chains of the heterologous duplex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

1976
1976
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…1). Thus the amounts of sequence divergence observed between Atriplex species are distinctly larger than intrageneric divergence values measured for species of sea urchin (Angerer eta!., 1976;Harpold and Craig, 1978), deer mouse (Rice, 1972), Junco (Shields and Straus, 1975), black flies (Sohn et al, 1975) or salamander (Mizuno and MacGregor, 1974). Our divergence estimates for Atriplex are also greater than those reported for Lathyrus species (Narayan and Rees, 1977) and greater than or equal to those observed in the genus Osmunda (Stein etal., 1979).…”
Section: Discussior'i (I) Intergeneric Hybridscontrasting
confidence: 53%
“…1). Thus the amounts of sequence divergence observed between Atriplex species are distinctly larger than intrageneric divergence values measured for species of sea urchin (Angerer eta!., 1976;Harpold and Craig, 1978), deer mouse (Rice, 1972), Junco (Shields and Straus, 1975), black flies (Sohn et al, 1975) or salamander (Mizuno and MacGregor, 1974). Our divergence estimates for Atriplex are also greater than those reported for Lathyrus species (Narayan and Rees, 1977) and greater than or equal to those observed in the genus Osmunda (Stein etal., 1979).…”
Section: Discussior'i (I) Intergeneric Hybridscontrasting
confidence: 53%
“…Another in vitro DNA labelling method, namely radioiodination (125I) of DNA according to the reaction of Commerford (1971) has been applied frequently in recent years, for instance by Sohn, Rothfels & Straus (1975), Stein, Thompson & Belford (1979), de Bont et al (1980), Lachance (1980) and Triantaphyllidis & Richardson (1982).…”
Section: Labelling and The Nature Of The Labelled Productmentioning
confidence: 99%
“…This technique was also applied to the taxonomy of a variety of organisms: hominids (Kohne, Chiscon & Hoyer, 1971), salamanders (Mizuno & Macgregor, 1974), Drosophila (Hunt, Hall & Britten, 198 l;Triantaphyllidis & Richardson, 1982), black flies (Sohn, Rothfels & Straus, 1975), Crustacea (Vaughn & Treager, 1976), sea urchins (Angerer, Davidson & Britten, 1976;Britten, Cetta & Davidson, 1978;Hall et al, 1980), Protozoa (Allen & Li, 1974), angiosperms (Bendich & McCarthy, 1970;Flavell, Rimpeau & Smith, 1977;Belford & Thompson, 1981a, b), and ferns (Stein, Thompson & Belford, 1979).…”
mentioning
confidence: 99%
“…Thermal stability profiles of interspecific DNA hybrids can be used to calculate the extent to which single base changes have accumulated in the DNA forming hybrid duplexes. To date, hybridization has been employed to examine DNA sequence evolution in several animal groups such as primates (Kohne, 1970), artiodactyls (Laird et al, 1969), mice (Rice, 1972), birds (Shields and Straus, 1975;Sibley and Ahiquist, 1980), flies (Sohn et a!., 1975), and salamanders (Mizuno and MacGregor, 1974). In general, it is observed that within a genus nearly all single copy DNA sequences (80-100 per cent) are represented in every species, though with somewhat (0-3 per cent) modified sequence.…”
Section: Introductionmentioning
confidence: 99%